منهج الدّعاة المعاصرين في الدّعوة عبر وسائل التّواصل الاجتماعيّ (الفيسبوك وتويتر): The Approach of Contemporary Preachers in Dawah through Social Media Platforms (Facebook and Twitter) - Mohammad, Loyi; Abdul Kadir, Fakhrul Adabi; Hameed Qatawneh, Mohammad Abdul (Al-Basirah Journal, 2025)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="9acdad57-0371-4e8e-90d3-c8aaca10d1cf" data-message-model-slug="gpt-4o"> This study examines influential Daw’aa (Islamic preaching) models within the Arab community, specifically focusing on preacher Mustafa Hosny and preacher Mohammad Ratib Al-Nabulsi. As for the broader non-Muslim audience, the most prominent model is preacher Zakir Naik, who has dedicated himself to inviting non-Muslims to Islam and correcting misconceptions about the religion. The study aims to evaluate the social media pages (Facebook and Twitter) of the most renowned contemporary preachers in the field of Daw’aa (Islamic preaching), analyzing their methods, particularly those with a high following and significant engagement on social media platforms. This is achieved by reviewing their accounts on these two platforms. The study’s key findings highlight that contemporary preachers present diverse Daw’aa content on social media, incorporating various Daw’aa themes in terms of both form and substance. This diversity reflects their deep awareness and understanding of audience needs. The analysis of Daw’aa methodologies among the selected preachers reveals that each preacher adopts a unique Daw’aa approach that distinguishes them from others. This diversity in Daw’aa methods is crucial to meeting the varying needs and expectations of different audiences, ensuring alignment with their intellectual, cognitive, and psychological capacities, and effectively engaging the targeted Daw’aa demographics.